Formação profissional para a humanização na saúde: contribuições de Sigmund Freud - Porto, Alana Brandelero (2023)
Humanization is one of the issues that is present, to some extent, for all human beings. An individual becomes human when they understand that this unique status is not naturally given. However, the way to remain human, or how to preserve human life in its dignity, are questions that arise, and from them, answers are forged with the intention of addressing these existential questions. Various classical and contemporary authors, from philosophy to psychoanalysis, directly address the theme or are sought, in their originality, to contribute to answers regarding humanization as a practice and as ethics. In the realm of healthcare, it is possible to see that the idea of humanization accompanies the official documents of the country as academic discussions have emerged since the early 21st century. The present dissertation aims, based on documentary and bibliographic research with a hermeneutic orientation, to understand Freud's proposition about the human condition with the purpose of thinking about the training of healthcare professionals with a view to humanizing healthcare practices. As a research guideline, the following question is raised: How is the idea of humanization inscribed in the field of health, and how can Freud's understanding of the human condition contribute to thinking about the training of healthcare professionals in a humanized way, with respect to care practices in institutions? The text is divided into two parts. In the first part, the construction of health and the directions of (de)humanization are revisited through an examination of the concept of health in history, health in Brazil, the notion of humanization in healthcare, and a problematization of the production of (de)humanization. In the second part, possible contributions of Sigmund Freud to the humanization of healthcare professionals are presented, with two important texts from his work as the main references, namely, the "Project for a Scientific Psychology" (1895) and "The Uncanny" (1919). Initially, a justification is provided for choosing Freud as a research reference. Then, these two texts by the author are explored with the intention of finding conceptual tools in them to broaden the debate on humanization. In the first Freudian text, the notion of humanization extracted from it leads us to consider it as an entry and permanence in the realm of ethical existence, resulting from the altruistic gesture of embracing the initial helplessness that marks the human condition. In the second text, the human condition is also evident as an ethical existence that requires attention to the uncanny and barbaric within us, even though it may frighten us. Based on these texts, the potential of Freudian ideas for the training of healthcare professionals with a view to humanization is considered, and the care for the self-formation process needs to exist and be part of the constitution of the human being in the world. This individual needs to reach their own subjectivity, but, especially, be oriented towards the humanization of the individual as a caregiving professional and extended to those being cared for in the context of healthcare. In conclusion, it was possible to establish that Freud's understanding of the human condition can contribute to thinking about the training of healthcare professionals in a humanized way with regard to care practices in institutions